LINGUOCULTURAL RESEARCH OF PHRASEOLOGICAL UNITS - Mirzayeva Gulnozaxon Ilxamovna (PEDAGOGS, 2024)
Abstract: The study of phraseological units based on linguocultural theory, the connection between language and culture, and the uniqueness of national mentalities are the main topics of this article. Understanding national mentalities and the relationship between language and culture necessitate a thorough and rigorous investigation of the fundamentals of language and its communication role. Studying different languages enables you to learn about and, if at all possible, experience the culture of that country. In this way, the study of how language and culture interact has recently gained a lot of attention.